Hukuk ve ekonomi öğretisi ve haksız fiil hukukunun ekonomik analizi - Sanlı, Kerem Cem (My University, 2006)
TEZ ÖZETİ Hukuk ve ekonomi öğretisi, bugün başta ABD olmak üzere yabancı hukuk sistemlerinde en etkili düşünce akımlarının başında gelmektedir. Hukuk ve ekonomi öğretisi, hukukun ekonomik analizini konu alır. Hukukun ekonomik analizi ise, kişinin rasyonel olarak faydasını maksimize etme eğiliminde olduğunu varsayılarak, hukuk kurallarının kişinin saik ve davranışları üzerindeki etkilerini incelenmesini ifade eder. Mesela haksız fiil hukuku kurallarının kişileri özenli davranmaya sevk edip etmediği veya kusur ve kusursuz sorumluluk kurallarının bu açıdan gösterdiği özellikler buna örnektir. Tezin temel amacı bu öğreti ve öğretinin dayandığı temel prensip, yöntem ve kavramlarının tanıtılmasıdır. Nitekim ilk bölüm, ekonomik analizin temel kavramlarına ayrılmıştır. Bu çerçevede analizde yararlanılan davranış teorileri, piyasa, arz, talep, maliyet, sosyal refah, ekonomik etkinlik gibi, temel kavramlar açıklanmıştır. Hukukun ekonomik analizini açıklamanın en iyi yöntemi, analizi belirli bir hukuk alanında tatbik etmektir. Bu hususta ise, ekonomik analizin en başarılı uygulama alanı olarak kabul edilen haksız fiil hukuku seçilmiştir. Haksız fiil hukukunun ekonomik analizi üç bölümde yapılmıştır. İlk bölüm, ekonomik açıdan haksız fiil hukukuna giriş olarak nitelendirilebilir. Bu bölümdeki ilk paragraf, haksız fiil hukukunun ekonomik açıdan hangi sorunu düzenlendiğini ve bu sorunun çözümünde haksız fiil hukukukunun işlevini izah etmektedir. İkinci paragraf, haksız fiil hukukuna atfedilen amacı konu almaktadır. Önce Türk hukuk doktrininin “amaç” sorununa yaklaşımı eleştirilmiş; akabinde haksız fiil hukukuna atfedilen amacın neden isabetli olmadığı açıklanmıştır. Diğer bölüm, haksız fiil hukukuna atfedilen amaç dikkate alınarak kusur, nedensellik, zarar ve hukuka aykırılık kavramlarının ekonomik açıdan yorumunu konu almaktadır. Paragrafların her birinde önce Türk hukukunda bu kavramlara nasıl yaklaşıldığı ve bu yaklaşımın eleştirisine yer verilmiş, akabinde ekonomik yorum yapılmıştır. Özel önem taşıyan paragraflar, kusur ve zarar başlıklarıdır. Kusur başlığında, “Hand formülüne” yer verilmiş ve formülün Türk hukukunda ihmalin tespitinde ne ölçüde uygulanabileceği incelenmiştir. Zarar bahsinde ise, bilhassa salt ekonomik zarar sorunsalı incelenmiş ve ekonomik teorinin sağlayabileceği muhtemel katkı araştırılmıştır. Son bölüm, hukuki kurumsal yapı sorununu konu almaktadır. Burada öncelikle kurumsal yapı olarak haksız fiil hukukunun hangi hallerde uygulanmasının daha isabetli olabileceği incelenmiştir. Akabinde ise, kusur ve kusursuz sorumluluk kuralları sosyal refah açısından incelenmiş ve bazı somut çıkarımlarda bulunulmuştur.

Law and economics has been one of the most successful innovations in the legal academy in the last century. The term Law and Economics refers to a body of scholarship whose objective is to apply the insights of modern economics to the full range of the law, i.e. the system of legal rules which underpin various societies. The application of economics to law can not only help us explain how legal rules evolve, but also what the consequences of alternative rules might be. If one assumes that individuals are rational and seek to maximize their utility, it becomes possible to forecast the social effects of laws. For instance, one could compare the negligence and strict liability rules, in terms of effects on safety and accident levels. Law and Economics therefore uses economic analysis as a way of evaluating these rules by questioning how well they serve particular social objectives, i.e. how efficient they are. The main purpose of this thesis is to explain the main tenets of economic analysis of law and to introduce the Turkish legal academia to this relatively new field of law. Mainly to serve this purpose, the first part is devoted to the main concepts of economic analysis such as rational choice theory, expected utility theory, opportunity cost, efficiency, social welfare, wealth maximization etc. Probably the best way to explain economic analysis is to apply economic principles to certain field of law. In that regard, tort law is considered to be the best candidate for economic analysis given that the norms are vague and there is a vast literature in the scholarship. We categorize our analysis into three parts. The first part could be labeled as the introduction to the economic analysis of torts. Law and economics explains tort law as that body of rules designed to minimize the social costs of accidents, defined as the sum of prevention, accident, and administrative costs. By holding out the possibility of imposing liability on a party for the costs of accidents, tort law seeks to get both potential injurers and potential victims to internalize the costs that their actions or failures to act may impose on others. This possibility induces rational parties to take all cost-justified care-- i.e., to purchase precaution up to the point at which the marginal benefit of that precaution (in terms of the reduced probability and severity of an accident) equals the marginal cost. Doing so minimizes the social costs of accidents. Given the economic purpose of tort law, it is possible to interpret the basic concepts of Tort law from economic perspective. Hence the second part is devoted to the economic interpretation of negligence, causality, damage and wrongfulness (illegality) within this framework. In each paragraph, initially the classical Turkish legal approach is defined, then this approach is criticized and finally legal concepts are rationalized and defined from economic perspective. I believe two paragraphs are particularly important. The first one is apparently economic definition of negligence: namely “Hand formula”. The other one is the concept of “pure economic loss”. Economic theory provides valuable insights in understanding the actual operation of both concepts in Tort Law. The last part covers the problem of institutional choice when dealing with externalities. After examining the comparative advantage of tort law as an institutional structure in law enforcement, negligence and strict liability are compared in terms of social welfare effects.
Keywords: Hukuk_Ekonomi; Özel Hukuk